Effect of Shaking Amplitude and Capturing Height on Mechanical Harvesting of Fresh Market Apples. Issue 30 (2019) - Fu, Han; Duan, Jieli; Karkee, Manoj; He, Long; Xia, Hongmei; Li, Jun; Zhang, Qin
Abstract: This study evaluated the effect of shaking amplitude and capturing height on mechanical harvesting of fresh market apples in trellis trained trees. A linear-forced limb shaker with adjustable shaking amplitude and frequency was designed and fabricated. Shaking amplitudes of 20, 25, 30, 35 and 40 mm were accessible. A catcher filled with 50 mm thickness of peanut foam underneath a piece of cotton was developed. The shaker and the catcher mounted on a movable lifting platform were integrated into a shake-and-catch harvesting system. The approximate middle of a targeted limb was selected as the shaking point and detached fruits were captured underneath the targeted section. The overall combinations of five levels of shaking amplitude and two levels of capturing height were tested for 'Pink Lady' apple trees trellis trained in a vertical fruiting wall architecture. Shaking frequency with 20 Hz and duration with 5 s were used in all tests. Fruit removal efficiency and fruit quality (USDA standard) were adopted to evaluate the quality of the harvesting system. Statistical analysis shows that fruit removal efficiency was significantly improved with increase of amplitude at a certain range; the capturing height significantly affected the percentage of Extra Fancy grade fruit. The results indicated that shaking amplitude with ~30 mm is sufficient to remove majority of fruits in the tested variety; capturing fruits that are much closer to the targeted limb is promising to obtain more Extra Fancy grade fruit.